The mediating effects of implied volatility and exchange rate on the U.S. tourism-growth nexus - Pat Obi; Godwin-Charles Ogbeide (Journal of Risk and Financial Management, 2022)
In this paper, we examine the impact of destination risk and currency valuation on the U.S. tourism-growth nexus using the recently developed nonlinear autoregressive distributed lag cointegration technique. Tourism development is proxied by tourist arrivals, while growth is measured by real GDP. Empirical results show evidence of long-run asymmetric bidirectional causality. Positive shocks in tourism development directly impact growth, while negative shocks in GDP have a negative causal effect on tourism. This latter finding, which supports the growth-led tourism hypothesis, suggests that in the long run, tourism tends to improve following periods of economic weakness, perhaps due to the dollar's weakness at such times. However, we have evidence only of unidirectional causality running from GDP to tourism in the short run. An important implication of these findings is the need to promote inbound tourism, especially when weakness in the U.S. economy is accompanied by a decline in the value of the dollar.
Keywords: 330; tourism development; implied volatility; NARDL; asymmetric causality; cointegration